Characteristics of children with ataxic cerebral palsy - Katina Pettersson; Mette Johansen; Reidun Jahnsen; Elisabet Rodby-Bousquet (BMC Pediatrics)
Abstract Background To compare the characteristics, functional levels, and comorbidities of children with ataxic cerebral palsy (CP), with those of children with other CP subtypes. Methods A cross-sectional study of children with CP born between 2000 and 2019 as reported in the Scandinavian national CP follow-up programmes and quality registries. Data for age, sex, levels of the Gross Motor Function Classification System (GMFCS), the Manual Ability Classification System (MACS), the Communication Function Classification System (CFCS), epilepsy, intellectual disability, and pain were extracted. Results There were 302 children (3.9%) with ataxic CP and 7336 children (96.1%) with other subtypes. Children with ataxic CP differed significantly from other subtypes, with a greater proportion classified in GMFCS II (37.7% vs. 15%), MACS II (41.4% vs. 24.8%), and CFCS II (24.7% vs. 10.5%), more girls (50.7% vs. 41.7%), school-aged (47% vs. 41.6%), adolescents (33.4% vs. 25.4%), or had an intellectual disability (51.2% vs. 38.4%), but the prevalence of pain and epilepsy was similar between the subtypes. Conclusions Children with ataxic CP have different characteristics and functional levels than children with other subtypes. We recommend a thorough examination of motor performance, communication, and intellectual disability to meet the individual needs of children with ataxic CP.